Child-onset and adolescent-onset acquired thrombotic thrombocytopenic purpura with severe ADAMTS13 deficiency: a cohort study of the French national registry for thrombotic microangiopathy. Issue 11 (November 2016) - Joly, Bérangère S; Stepanian, Alain; Leblanc, Thierry; Hajage, David; Chambost, Hervé; Harambat, Jérôme; Fouyssac, Fanny; Guigonis, Vincent; Leverger, Guy; Ulinski, Tim; Kwon, Thérésa; Loirat, Chantal; et al.
Summary: Background: Thrombotic thrombocytopenic purpura is a rare thrombotic microangiopathy, related to a severe ADAMTS13 deficiency (a disintegrin and metalloprotease with thromboSpondin type 1 repeats, member 13; activity <10% of normal). Childhood-onset thrombotic thrombocytopenic purpura is very rare and initially often misdiagnosed, especially when ADAMTS13 deficiency is acquired (ie, not linked to inherited mutations of the ADAMTS13 gene). We aimed to investigate initial presentation, management, and outcome of acquired thrombotic thrombocytopenic purpura in children. Methods: Between Jan 1, 2000, and Dec 31, 2015, we studied a cohort of patients with child-onset and adolescent-onset acquired thrombotic thrombocytopenic purpura included in the French national registry for thrombotic microangiopathies at presentation and during follow up. The inclusion criteria were: first episode before age 18 years; ADAMTS13 activity less than 10% of normal at presentation; positive anti-ADAMTS13 autoantibodies during an episode, or a recovery of ADAMTS13 activity in remission, or both. ADAMTS13 activity and anti-ADAMTS13 autoantibodies were investigated by a central laboratory, and medical records were extensively reviewed to collect clinical and biological features with a standardised form. This study is registered withClinicalTrials.gov, numberNCT00426686 . Findings: We enrolled 973 patients with childhood-onset thrombotic microangiopathy, of whom 74 had a severe ADAMTS13 deficiency (activity <10%) at presentation. 24 patients had an inherited thrombotic thrombocytopenic purpura also known as Upshaw-Schulman syndrome and five did not have follow-up data available, thus 45 children had acquired thrombotic thrombocytopenic purpura and were included in our database at presentation. 25 (56%) patients had idiopathic disease and 20 (44%) had miscellaneous associated clinical conditions. At diagnosis, median age was 13 years (IQR 7–16, range 4 months–17 years), with a sex ratio of 2·5 girls to 1 boy. Anti-ADAMTS13 autoantibodies were positive in 37 (82%) of 45 patients (24 [96%] of 25 idiopathic cases and 13 [65%] of 20 non-idiopathic cases). 39 (87%) of 45 patients were given plasma therapy and 21 (47%) received additional rituximab. Four (9%) children died after the first thrombotic thrombocytopenic purpura episode. Long-term follow up of the 41 survivors showed that ten (24%) patients relapsed and systemic lupus erythematosus occurred in two (5%) patients. Preemptive rituximab was used in seven (17%) of 41 patients with acquired thrombotic thrombocytopenic purpura. Interpretation: Our study shows that child-onset and adolescent-onset acquired thrombotic thrombocytopenic purpura have specific clinical, biological and therapeutic features. Long-term follow-up is crucial to prevent relapses of the disease, to identify the occurrence of autoimmune disorders, and to evaluate consequences on social life. Child-onset and adolescent-onset acquired thrombotic thrombocytopenic purpura is a crucial diagnosis in the field of paediatric haematologic cytopenias because it is a life-threatening disease requiring a specific management. Funding: Assistance Publique-Hôpitaux de Paris, France.